Hubungan Pengetahuan dan Sikap Ibu dengan Kelengkapan Imunisasi Dasar di Desa Suka Raya Kecamatan Pancur Batu Tahun 2024 - Kaminya Zai; Elvipson Sinaga (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Immunization Completeness base is an immunization that must be given to children from birth so that their bodies are protected from dangerous diseases. Complete basic immunization coverage in Suka Raya Village, Pancur Batu District reached 80.7%: the low coverage of basic immunization is related to the knowledge and attitudes of mothers. This study aims to determine the relationship between maternal knowledge and attitudes and the completeness of basic immunization in infants . Data collection from primary and secondary data, data were analyzed using the chi-square test with a 95% confidence level. This type of research is analytical with a Cross Sectional approach , the population in this study were all mothers who had babies aged 9-12 months who visited Suka Raya Village, namely 42 people. The sampling technique is Total Sampling . Collection data For about complete basic immunization data analysis with Chi Square statistical test . The results of the study showed that there was a relationship between maternal knowledge and attitudes with the completeness of basic immunization with a p value for the knowledge variable of 0.003 and a p value for the attitude variable of 0.000. Then, maternal knowledge and attitudes influenced the completeness of basic immunization in infants, mothers with good knowledge and positive attitudes were more likely to complete their infants' basic immunization according to the specified schedule. It is recommended for Pancur Batu Village to further improve the provision of counseling to mothers about complete basic immunization and for health workers in Pancur Batu Village to improve maternal knowledge about the completeness of basic immunization